Media Konstruksi Berpikir Kritis Berbasis Praktik Literasi pada Pembelajaran Bahasa Indonesia di Sekolah Dasar Era Merdeka Belajar - Della Yunia Amami; Lilik Wahyuni (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2022)
This study aims to develop critical thinking construction media based on literacy practices on Indonesian learning and describe the impact of media implementation on students' critical thinking skills. The research method used is the Research & Development (R&D) ADDIE model. The study was conducted at SDN Balearjosari 1 with the subject of the study being a grade IV. Data collection are carried out through the provision of questionnaires to validators, students, and teachers. Data analysis techniques use quantitative and qualitative techniques. Literacy-based critical thinking construction media was developed based on the ADDIE model which obtained assessments from media experts and material experts. The media expert validation results are 86% and the material expert validation results are 88% with the category of very feasible. This means the implementation of literacy-based critical thinking construction media is assessed from the aspect of the media and the material can be used as a new innovation for learning. The impact of media implementation on students' critical thinking skills has increased which seen through the results of literacy work projects and improvements in 6C competencies. In addition to having an impact on critical thinking skills, literacy practices also improve literacy skills and foster student learning motivation.